Note on Occlusion of Resin Channels in a Chir Pine Tree - Joshi, H. B. (Indian Forester, 1975)
Observations made on the occlusion of resin-channels on a single tree of Pinus roxburghii Sarg. (Chir pine) tapped for resin under light continuous system for 42 years are given. The data indicate that under such tapping, a quinquennial channel is occluded in about 30 years, occlusion rate being highest at the top and bottom of the channel and least in the middle zone. Occlusion rate is adversely affected if channel width and depth exceed the prescribed standards, more so if severe fires run over the channels. Under standard light tapping conditions old channels are occluded by the time a second round of tapping starts and if the tree is still unfelled, there is space even for a third round of tapping.